Impact of cryoballoon application abortion due to phrenic nerve injury on reconnection rates: a YETI subgroup analysis. Issue 2 (23rd November 2022) - Heeger, Christian-H; Popescu, Sorin Ștefan; Sohns, Christian; Pott, Alexander; Metzner, Andreas; Inaba, Osamu; Straube, Florian; Kuniss, Malte; Aryana, Arash; Miyazaki, Shinsuke; Cay, Serkan; Ehrlich, Joachim R; et al.
Abstract: Aims: Cryoballoon (CB)-based pulmonary vein isolation (PVI) is an effective treatment for atrial fibrillation (AF). The most frequent complication during CB-based PVI is right-sided phrenic nerve injury (PNI) which is leading to premature abortion of the freeze cycle. Here, we analysed reconnection rates after CB-based PVI and PNI in a large-scale population during repeat procedures. Methods and results: In the YETI registry, a total of 17 356 patients underwent CB-based PVI in 33 centres, and 731 (4.2%) patients experienced PNI. A total of 111/731 (15.2%) patients received a repeat procedure for treatment of recurrent AF. In 94/111 (84.7%) patients data on repeat procedures were available. A total of 89/94 (94.7%) index pulmonary veins (PVs) have been isolated during the initial PVI. During repeat procedures, 22 (24.7%) of initially isolated index PVs showed reconnection. The use of a double stop technique did non influence the PV reconnection rate ( P = 0.464). The time to PNI was 140.5 ± 45.1 s in patients with persistent PVI and 133.5 ± 53.8 s in patients with reconnection ( P = 0.559). No differences were noted between the two populations in terms of CB temperature at the time of PNI ( P = 0.362). The only parameter associated with isolation durability was CB temperature after 30 s of freezing. The PV reconnection did not influence the time to AF recurrence. Conclusion: In patients with cryoballon application abortion due to PNI, a high rate of persistent PVI rate was found at repeat procedures. Our data may help to identify the optimal dosing protocol in CB-based PVI procedures. Clinical Trial Registration: https://clinicaltrials.gov/ct2/show/NCT03645577?term=YETI&cntry=DE&draw=2&rank=1 ClinicalTrials.gov Identifier: NCT03645577.